Two-dimensional infrared spectroscopy reveals cosolvent-composition-dependent crossover in intermolecular hydrogen bond dynamics - Kashid, Somnath M.; Jin, Geun Young; Chakrabarty, Suman; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2017)
Cosolvents have versatile composition-dependent applications in chemistry and biology. The simultaneous presence of hydrophobic and hydrophilic groups in dimethyl sulfoxide (DMSO), an industrially important amphiphilic cosolvent, when combined with the unique properties of water, plays key roles in the diverse fields of pharmacology, cryoprotection, and cell biology. Moreover, molecules dissolved in aqueous DMSO exhibit an anomalous concentration-dependent nonmonotonic behavior in stability and activity near a critical DMSO mole fraction of 0.15. An experimental identification of the origin of this anomaly can lead to newer chemical and biological applications. We report a direct spectroscopic observation of the anomalous behavior using ultrafast twodimensional infrared spectroscopy experiments. Our results demonstrate the cosolventconcentration-dependent nonmonotonicity arises from nonidentical mechanisms in ultrafast hydrogen-bond-exchange dynamics of water above and below the critical cosolvent concentration. Comparison of experimental and theoretical results provides a molecular-level mechanistic understanding: a distinct difference in the stabilization of the solute through dynamic solute solvent interactions is the key to the anomalous behavior.

Transition of a deep eutectic solution to aqueous solution: a dynamical perspective of the dissolved solute - Sakpal, Sushil S.; Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2021)
Disruption of the deep eutectic solvent (DES) nanostructure around the dissolved solute upon addition of water is investigated by polarization-selective two-dimensional infrared spectroscopy and molecular dynamics simulations. The heterogeneous DES nanostructure around the solute is partially retained up to 41 wt % of added water, although water molecules are gradually incorporated in the solute's solvation shell even at lower hydration levels. Beyond 41 wt %, the solute is observed to be preferentially solvated by water. This composition denotes the upper hydration limit of the deep eutectic solvent above which the solute senses an aqueous solvation environment. Interestingly, our results indicate that the transition from a deep eutectic solvation environment to an aqueous one around the dissolved solute can happen at a hydration level lower than that reported for the ``water in DES'' to ``DES in water'' transition.